Run-prone banking and asset markets - Marie Hoerova (European Central Bank (ECB), 2007)
I analyze the role that asset markets play in the performance and stability of the run-prone banking sector. Banks insure consumers against privately observed liquidity shocks. Asset market investments insure consumers against losses from bank runs. If the probability of a run is small, then banks specialize fully into the provision of liquidity insurance: They provide a higher degree of liquidity insurance when compared to the economy with banks alone. If the probability of a run is high, consumers prefer to invest solely through the asset market. Insurance against runs provided by the market investment reduces consumers' incentives to run. Increased provision of liquidity insurance by banks has the opposite effect. I derive conditions under which the latter effect dominates and the probability of a run is higher than with banks alone.
Keywords: E44; G21; 330; asset markets; Bank runs; financial stability; liquidity; Mechanism Design; Bankenliquidität; Bankenkrise; Finanzmarkt; Theorie